THE ANALYSIS OF FACTORS THAT AFFECT LABOR ABSORPTION IN NATURAL RUBBER PLANTATION - Nadya Putri; Heri Sudarsono (Universitas Muhammadiyah Ponorogo, 2019)
The study aimed to analyze several indicators that exist in the rubber industry and their influence on labor absorption in particular provinces in Indonesia from 2012-2015. The provinces consisted of North Sumatera, Riau, South Sumatera, Lampung, West Kalimantan, Central Kalimantan, South Kalimantan, West Java, Aceh, and East Java. The factors that the writer used in this research were rubber production, the size of rubber plantation, provincial minimum wage, and the number of company. In this research, the writer used panel data regression as the analyzing tool and random effect model as the best model to describe the relationship between independent and dependent variables. The result of the result shows that the provincial minimum wage and the number of company had significant effect on labor absorption while the other two, rubber production and the size of rubber plantation area did not have significant effect on labor absorption.